Ethiopian Students’ Perceptions of Learner-centered Grammar Teaching Methodology in Some Secondary Schools of Oromia Special Zone Surrounding Finfinne - Tamirat Tesfaye Diyessa; Abebe Gebretsadik Woldearegawi (English Department - University of Sultan Ageng Tirtayasa, 2024)
The purpose of this study was to investigate students’ perceptions on the advantages of learner-centered approaches and grammar teaching methods in secondary schools. The study utilized descriptive research design, employing a questionnaire and an interview. Two hundred grade 9 students for the questionnaire and six students for an interview were randomly selected. Questionnaire data was analyzed using mean and standard deviation. The interview data was analyzed thematically to support the questionnaire data. The findings of the study revealed students had positive perceptions on some of the learner-centered-methods of grammar presentation because they believe that these methods help them to become users of the language for communication. However, they had negative perceptions on some of them. As a result, they were more interested in grammar explanation by their teachers since they were accustomed by lecture method. Implications suggest that teachers should make students active participants by bringing various grammar tasks that arouse students’ interests; they should practice learner-centered methods namely pair work, group work, asking and answering questions and situational dialogue in order to build students’ confidence.